Economic news releases and financial markets in South Africa - Konstantinos Gkillas Gillas; Dimitrios I. Vortelinos; Christos Floros; Athanasios Tsagkanos (Economies, 2019)
We examine the impact of economic news releases on returns, volatility and jumps of the stock and foreign exchange markets of South Africa. We also assess the impact of macroeconomic determinants. The dataset range is fifteen years covering the period from January, 2000 to December, 2014. Results are robust to different sub-periods before and after the global financial crisis of 2008. Volatility is estimated with the use of the median realized variance estimator (()). Jumps are detected and estimated as in . The impact of the announcements is assessed building on the study by . Returns, volatility and jumps of both stock and foreign exchange markets are significantly explained nationally by macroeconomic fundamentals and economic news releases.
Keywords: G15; G18; F38; 330; economic news; macro fundamentals; South Africa